Step
*
of Lemma
rless-iff
∀x,y:ℝ.  (x < y 
⇐⇒ ∃n:ℕ+. ∀m:ℕ+. ((n ≤ m) 
⇒ (m ≤ (n * ((y m) - x m)))))
BY
{ (InstLemma `regular-less-iff` [] THEN Fold `rless` (-1) THEN RepeatFor 3 (ParallelLast')) }
1
1. x : ℝ
2. y : ℝ
3. x < y
4. ∀b:{4...}. ∃n:ℕ+. ∀m:{n...}. (x m) + b < y m
⊢ ∃n:ℕ+. ∀m:ℕ+. ((n ≤ m) 
⇒ (m ≤ (n * ((y m) - x m))))
2
.....antecedent..... 
1. x : ℝ
2. y : ℝ
3. ∃n:ℕ+. ∀m:ℕ+. ((n ≤ m) 
⇒ (m ≤ (n * ((y m) - x m))))
⊢ ∀b:{4...}. ∃n:ℕ+. ∀m:{n...}. (x m) + b < y m
Latex:
Latex:
\mforall{}x,y:\mBbbR{}.    (x  <  y  \mLeftarrow{}{}\mRightarrow{}  \mexists{}n:\mBbbN{}\msupplus{}.  \mforall{}m:\mBbbN{}\msupplus{}.  ((n  \mleq{}  m)  {}\mRightarrow{}  (m  \mleq{}  (n  *  ((y  m)  -  x  m)))))
By
Latex:
(InstLemma  `regular-less-iff`  []  THEN  Fold  `rless`  (-1)  THEN  RepeatFor  3  (ParallelLast'))
Home
Index